Course of diabetic retinopathy following cataract surgery. - Pollack, A (1991)
Five patients with mild to moderate retinopathy to both eyes underwent complication-free cataract surgery in one eye. Within three months of surgery deterioration of the retinopathy was observed in the operated eye only. In four patients there was an increase of intraretinal haemorrhages and hard exudates, accompanied by clinically significant macular oedema manifested as retinal thickening and extensive fluorescein leakage from both the macular and the peripapillary capillary networks. Of these four patients one also developed retinal ischaemia, evident ophthalmoscopically by flame-shaped haemorrhages and cotton-wool spots and angiographically by areas of capillary non-perfusion. The fifth patient showed proliferation of new blood vessels and vitreous haemorrhage. Diabetic patients scheduled for cataract surgery should undergo a thorough preoperative evaluation of any existing retinopathy. Postoperatively they should be followed up at close intervals so that any progression of retinopathy can be promptly detected and considered for laser treatment.